Effect of the harvest season on the chemical characteristics of the sugar beet pulp (Beta vulgaris) granulated. Technical note - Arce, O. N.; Alagón, G.; Ródenas, L.; Martínez-Paredes, E.; Moya, V. J.; Pascual, J. J.; Cervera, C. (Cuban Journal of Agricultural Science, 2019)
The chemical composition of granulated beet pulps, from the north and south of Spain, harvested in winter and summer, respectively, was characterized. The chemical composition and the content of fatty acids and amino acids of 12 samples of beet pulp were compared grouped according to their origin. The winter and summer pulps differed in the content of insoluble ash (P <0.05), neutral detergent fiber (P <0.05), soluble fiber in neutral detergent (P <0.01) and starch (P <0.01). The content of crude protein and amino acids was low, as well as that of fat, whose most representative fatty acids were linoleic, palmitic and oleic, and in any case showed differences between groups. The analysis of the main components showed that the fiber soluble in neutral detergent and the insoluble fibrous components (neutral detergent fiber and acid detergent fiber) explain 61.6 % of the variability in the beet pulp composition. It is concluded that beet pulp from the sugar industry in Spain is a by-product that provides high fiber content, soluble as insoluble, although it is important to typify the chemical nature of these fibrous components, given their variability according to origin. Key words: fatty acids, amino acids, insoluble fiber, soluble fiber, beet pulp